Use of transvenous biopsy of tumor thrombus for the diagnosis of Wilms tumor - Krista Lai; Tj Wilson; Juan P. Gurria; Scott Willard; David Carpentieri; Benjamin E. Padilla (Elsevier, 2022)
Wilms tumor (WT) accounts for 90% of renal malignancies in children. Surgical resection is the mainstay of treatment, but neoadjuvant chemotherapy is considered in certain cases of tumor thrombus [1,2]. In North America, tumor biopsies are generally performed prior to initiating neoadjuvant chemotherapy. This report describes a case of a 7-year-old boy who presented with an abdominal mass and gross hematuria. An abdominal ultrasound and CT scan revealed a 9 cm right-sided renal mass most consistent with Wilms tumor. A near obstructing tumor thrombus was identified in the inferior vena cava (IVC) from the right renal vein to the confluence of the hepatic veins. In consultation with oncology and according to Children's Oncology Group (COG) recommendations [2], a biopsy was performed prior to initiating neoadjuvant chemotherapy. An endovascular, transvenous biopsy of the tumor thrombus was performed. In this case, a transvenous biopsy of the IVC tumor thrombus was an alternative technique that yielded adequate tissue to establish the diagnosis of Wilms tumor including histologic sub-classification and LOH status.